2022
DOI: 10.3389/fmars.2022.973155
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic effects of large-scale suspended mussel farms: Field observations and numerical simulations

Abstract: The hydrodynamic effects of the largest suspended mussel farms in the East China Sea near Gouqi Island, was investigated using a high-resolution 3D ocean model and field observations. To capture the 3D farm effects on hydrodynamics, an additional depth dependent momentum sink term was introduced in the model. The model results compared well with the field observations. The present model and observational results indicate that the presence of farms reduces the flow by more than 79%, 55%, and 34% in the upper, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Hydrodynamic conditions are pivotal in influencing sediment resuspension. Field observation and numerical simulation revealed that the current velocities at the surface, middle, and bottom layers in the mussel farms decreased by 80%, 55%, and 45%, respectively, attributable to the presence of culture rafts and ropes [25,54]. Therefore, a mussel farm with stable hydrodynamic conditions inhibits the resuspension of surface sediments, leading to lower SPM levels and high organic matter preservation within the mussel farm.…”
Section: Preservation Of Particulate Organic Matter and The Effects O...mentioning
confidence: 98%
See 1 more Smart Citation
“…Hydrodynamic conditions are pivotal in influencing sediment resuspension. Field observation and numerical simulation revealed that the current velocities at the surface, middle, and bottom layers in the mussel farms decreased by 80%, 55%, and 45%, respectively, attributable to the presence of culture rafts and ropes [25,54]. Therefore, a mussel farm with stable hydrodynamic conditions inhibits the resuspension of surface sediments, leading to lower SPM levels and high organic matter preservation within the mussel farm.…”
Section: Preservation Of Particulate Organic Matter and The Effects O...mentioning
confidence: 98%
“…Gouqi Island, located in the northeastern part of the islands in Zhoushan City, Zhejiang Province, China, is a typical region for shellfish mariculture. This island is at the heart of the Zhoushan Fishery, boasting a mussel farming area exceeding 12 km 2 and annual production of over 180,000 tons [25]. The dominant species, Mytilus coruscus, is cultivated using raft culture techniques that do not require additional feed.…”
Section: Introductionmentioning
confidence: 99%
“…Suspended longline form was adopted to culture mussels in Gouqi Island, which is consist of a buoy, mussel ropes, longline, mooring line and anchor block (Lin et al, 2016b;Zhong et al, 2022). Suspended culture can keep the shellfish on the surface of the ocean with plenty of natural food and protect it from predators (Mascorda Cabre et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted studies on the hydrodynamic characteristics of the suspended aquaculture farm. Field observations and large-scale numerical simulations have previously demonstrated that aquaculture farms can influence tidal flow at the scale of bays and the open ocean (Stevens et al, 2007;Plew, 2011a, b;Lin et al, 2016b;Liu and Huguenard, 2020;Zhong et al, 2022). Suspended shellfish farms induce current reduction of surface water layer (He et al, 2022), generate turbulence (Stevens and Petersen, 2011) and increase water exchange time (Liu and Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%